Geospatial analysis of risk components for elevated blood lead levels in Kansas: geologic and anthropogenic factors - Galinskaya, Karina (Kansas State University, 2018)
Children are the demographic most susceptible to and affected by lead poisoning. Lead contamination in soil has been recorded as being primarily from lead-based paint, historic leaded gasoline emissions, and from lead point-source emitters. The highest risk of elevated blood lead level (BLL) is correlated with living in an area dominated by pre-1950’s housing. From 1976 to 1994, midst the phasing out and removal of lead from gasoline, the blood lead levels of children in the United States decreased from 16 µg/dL to 3.2 µg/dL. There is evidence showing the irreversible effects of intellectual impairment still occur at levels of BLL below 10 µg/dL. In Kansas, Barton and Ellis counties residential soils were sampled, and chemical composition was examined with a handheld XRF and an HR ICP-MS. Particle size and pH were recorded for all samples. The presence or lack of of lead sulfate and lead carbonate was identified using XRD. Chemical tests revealed elevated Zn and As with increasing Pb concentrations. There was weak evidence of lead sulfate in one of eight tested samples. Barton county has courser sediments and the top five highest Pb concentrations recorded in this study. There is a significant correlation with Pb concentrations and age of housing for houses built prior to1950. Pb Isotopic analysis on eight samples showed multi-source contamination in the soil. We believe the source of most of the lead is from ambient lead mixed with historic leaded gasoline deposits and possible output from factories/coal, along with leaded paint in older homes. Three of the eight samples had paint chips which tested positive for lead. Maps were created showing central Kansas having elevated blood lead levels in children and overlays were made illustrating oil well density in counties. Five variables were used to create a risk assessment map for Kansas: housing age, poverty levels, blood lead levels, number of oil wells, and population.
Keywords: Lead; Blood lead levels; Risk assessment; Kansas